PERBEDAAN DUKUNGAN SOSIAL DARI IBU MERTUA PADA IBU MENYUSUI YANG BEKERJA DAN TIDAK BEKERJA - Purnamasari, Ayu Rakhmi Pris; Rahmatika, Rina (Faculty of Psychology, Diponegoro University, 2016)
Mother in law also has role to support the success of exclusive breastfeeding, beside biological mother. Thisstudy aimed to investigate differences between perceived breastfeeding social support from mother-in-law on working and not working-women. There are 200 sample of this study, which is divided to 2 groups of 100 working-women and 100 not working-women. Perceived breastfeeding social support scale (27 item, Î± = .95) is used in this study and it is constructed by using social-functional support theory. Result shows that there is significant differences between perceived breastfeeding social support from mother in law on working and notworking women (t (198)=2.42; p= .016; p < .05). Emotional support and informational support from mother-inlaw more perceived by not working women than working mom, in the other hand, working women and not working women have no different perception about instrumental support. Result of this study may be one of information that can be used to inform mother-in-law about how precious social support is to exclusive breastfeeding.